(untitled)
Abstract. This study investigates how Pancasila Education contributes to developing independent character in fifth-grade students at SDN 1 Kecapi. Employing a qualitative approach with a descriptive method, the findings indicate that Pancasila Education has been effectively implemented, from preparing learning materials that incorporate independence values to conducting activities that support character development. The use of the Project-Based Learning (PjBL) model positively influenced students’ understanding of Pancasila content as well as their social and character skills. Students became more critical, cooperative, responsible, and patriotic. This was evident in their heightened learning motivation, willingness to express opinions, and initiative in completing tasks autonomously. Observations and survey results also revealed that students could manage their time, carry out assignments without depending on teachers or peers, and demonstrate intrinsic motivation in acquiring knowledge and completing projects. In conclusion, implementing Pancasila Education through the PjBL approach substantially promotes student independence in both behavior and mindset, while highlighting the crucial role of teachers and the school environment in continually developing learning strategies that reinforce independent character. Keywords : Pancasila Education, Independent Character, Elementary School Abstrak. Penelitian ini bertujuan untuk menelaah peran pembelajaran Pendidikan Pancasila dalam membangun karakter mandiri pada siswa kelas V SDN 1 Kecapi. Penelitian dilakukan dengan metode kualitatif menggunakan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa pembelajaran Pendidikan Pancasila telah dijalankan dengan baik, mulai dari penyusunan perangkat ajar yang menanamkan nilai-nilai kemandirian hingga pelaksanaan kegiatan yang mendukung pembentukan karakter mandiri siswa. Penerapan model Project-Based Learning (PjBL) juga memberikan pengaruh positif terhadap pencapaian belajar siswa, baik dalam pemahaman materi Pendidikan Pancasila maupun dalam pengembangan keterampilan sosial dan karakter. Siswa menjadi lebih kritis, mampu bekerja sama, bertanggung jawab, serta menunjukkan rasa cinta tanah air. Hal ini terlihat dari peningkatan motivasi belajar, keberanian dalam mengemukakan pendapat, dan inisiatif dalam menyelesaikan tugas secara mandiri. Observasi dan hasil angket juga menunjukkan bahwa siswa dapat mengatur waktu, menyelesaikan tugas tanpa bergantung pada guru atau teman, serta memiliki motivasi internal untuk mencari informasi dan menyelesaikan proyek. Dengan demikian, pembelajaran Pendidikan Pancasila melalui pendekatan PjBL terbukti cukup efektif dalam membentuk siswa menjadi individu yang mandiri, sekaligus menegaskan pentingnya peran guru dan lingkungan sekolah dalam merancang strategi pembelajaran berkelanjutan untuk memperkuat karakter kemandirian peserta didik. Kata Kunci : Pendidikan Pancasila, Karakter Mandiri, Sekolah Dasar. , number=3, journal=Equilibrium: Jurnal Pendidikan, year=2025, month=Sep, pages=306–315